RETRACTED: Kinesin Family Member 2A Serves as a Potential Biomarker Reflecting More Frequent Lymph Node Metastasis and Tumor Recurrence Risk in Basal-Like Breast Cancer Patients - Yang, Hua; Liu, Yongjun (Frontiers in Surgery, 2022)
Background Kinesin family member 2A (KIF2A) is reported as an oncogene and a potential biomarker for progression and prognosis in several cancers such as cervical, ovarian, and gastric. However, its clinical value in basal-like breast cancer (BLBC) is unclear. This study aims to evaluate KIF2A expression and its correlation with clinical features and survival rates in BLBC patients. Methods KIF2A mRNA and protein expressions in tumor and adjacent tissues from 89 BLBC patients are assessed by reverse transcription-quantitative polymerase chain reaction and immunohistochemistry assays, respectively. Results Both KIF2A protein (p < 0.001) and mRNA expressions (p < 0.001) were higher in tumor than in adjacent tissue. Besides, tumor KIF2A protein expression was positively correlated with N (p = 0.028) and TNM (p = 0.014) stages; meanwhile, tumor KIF2A mRNA expression was positively correlated with N stage (p = 0.046), TNM stage (p = 0.006), and tumor size (p = 0.043). Additionally, both tumor KIF2A protein (p = 0.035) and mRNA (p = 0.039) high expressions were correlated with worse disease-free survival (DFS) but not with overall survival (both p > 0.05). Moreover, tumor KIF2A protein expression was higher in relapsed patients than in non-relapsed patients within 3 years (p = 0.015) and 5 years (p = 0.031), whereas no difference was found between the dead and survivors within 3 years (p = 0.057) or 5 years (p = 0.107). Lastly, after adjustment, tumor KIF2A mRNA high exhibited a trend that correlated with DFS but without statistical significance (p = 0.051). Conclusion KIF2A correlates with more frequent lymph node metastasis and worse DFS in BLBC patients, shedding light on its potency as a biomarker for BLBC.